Hypergraphs with infinitely many extremal constructions - Jianfeng Hou; Heng Li; Xizhi Liu; Dhruv Mubayi; Yixiao Zhang (Discrete Analysis, 2023)
Hypergraphs with infinitely many extremal constructions, Discrete Analysis 2023:18, 34 pp.